Simulation Analysis of Magnetic Characteristic of Double Permanent Magnet Wheel Linear Drive Device - Sun Feng; Ma Di; Zhao Chuan; Ren Huizhi; Xu Fangchao; Li Qiang; Jin Junjie (Jixie chuandong)
The non-contact permanent magnet force linear driving device of double permanent magnet wheel is a magnetic driving device for long-distance linear transmission by means of permanent magnet force. There is no direct surface contact between the double permanent magnet driving wheel and the iron rail rack，and the servo motor is controlled. The permanent magnet driving wheel is driven by the servo motor，and the device is driven by the magnetic force generated by the permanent magnet to the iron guide rack convex teeth. Firstly，the mathematical model of the magnetic force is established according to the structure of the dual permanent magnet wheel magnetic drive device. Secondly，the finite element method is used to simulate the horizontal driving force and the vertical interference force of the driving device，and the simulation result is compared with the single permanent magnet wheel driving device. The simulation results are compared and analyzed. Through comparative analysis，it is shown that the dual permanent magnet wheel non-contact permanent magnet force linear drive device not only eliminates the interference of longitudinal vertical interference force，but also increases the horizontal driving force of the driving device，and eliminates the backlash of the driving device during the driving process. The rail is balanced in the horizontal direction，which greatly improves the driving efficiency of the driving device.